On shadow banking and financial frictions in DSGE modeling - Philipp Kirchner (Philipps-University Marburg, School of Business and Economics, 2020)
At the forefront of macroeconomic research on the causes of the Great Financial Crisis (GFC) was and still is the usage of dynamic stochastic general equilibrium (DSGE) models. To capture the nonlinearities of the GFC, these models were enriched with a variety of fi…nancial frictions. This paper focuses on a special subset of these frictions, the shadow banking system. We provide a structured review of the strand of literature that considers shadow banking in DSGE setups and draw particular attention to the modeling approach as well as impact of shadow banking. Our analysis allows the following conclusions: fi…rstly, models featuring shadow banking are better able to simulate realistic movements in the business cycle that are of comparable magnitude to the GFC. Secondly, the models consider ampli…cation channels between the fi…nancial sector and the real economy that proved to be of importance during the crisis. Thirdly, the models display a good explanatory power of …financial stability measures in the light of shadow banking.
Keywords: E10; E44; E32; 330; Shadow Banking; DSGE; Financial Frictions; Financial Intermediation; Great Financial Crisis.